A robust FACTS PV-smart grid interface scheme for efficient energy utilisation. (2015) - Sharaf, Adel M.; Gandoman, Foad H.
In the last two decades, wind and PV system have been increased remarkably. A novel FACTS-based PV-DC-AC interface scheme using VSI-6 pulse scheme with a switched filter compensator (SFC) scheme developed by the first author is validated for efficient energy utilisation and decoupled DC-AC interface with robust stand under normal and faults (open and short circuit) conditions. The proposed FACTS scheme enhances power quality and ensures efficient energy utilisation and stabilised interface to the smart grid. The FACTS scheme is based on a hybrid power filter-capacitive compensation scheme with SPWM-dual switching strategy using a dual series and shunt capacitor banks. The hybrid control scheme uses a modified fast acting dynamic error driven time-descaled/decoupled multi-regulation loops with an additional inter-coupled weighted controller. The proposed FACTS-scheme is tested using the MATLAB-Simulink Simulation Environment. The unified AC study system was tested under different operating/fault conditions including normal loading and open/short circuit fault conditions.